Social Media Sentiment Analysis on Waqf and Education - Sukmana, Raditya; Rusydiana, Aam Slamet (SMART Insight, 2023)
This research aims to measure public sentiment towards waqf education by using primary data derived from Twitter tweets. Sentiment measurement utilizes a Python Library software called VADER (Valence Aware Dictionary and Sentiment Reasoner) to classify the sentiment in each tweet analyzed. The results revealed that India was the location with the highest tweet activity around waqf education, reaching a total of 656 tweets. The highest peak of tweet activity occurred in 2020, with 170 tweets during the study period. In terms of sentiment polarity, the majority of tweets showed positive sentiment (48.3%), followed by neutral sentiment (27.0%), and negative sentiment (24.8%). The importance of these findings lies in the in-depth understanding of how people respond to and perceive waqf education. This sentiment analysis can provide valuable insights for decision makers and relevant stakeholders in developing and improving waqf education practices in the future